SINGLE-SEX EDUCATION: DOES IT MAKE A DIFFERENCE TO STUDENTS’ ACADEMIC ACHIEVEMENT? - Surya Fajar Cahyo Nuraeni (IJIET (International Journal of Indonesian Education and Teaching), 2020)
Gender gap in education has been Indonesian government’s big concern (Bappenas, 2013). The Ministry of National Development Planning of Republic of Indonesia has reflected data showing gender gap in academic achievement among boys and girls in Indonesia. They also realize the importance of catering for gender differences during teaching and learning process. They believe that providing single-sex education is an effective way to narrow gender academic achievement gap in schools. In this paper, single-sex education, coeducational education, and academic achievement become the core concepts to analyse this issue. The result of this investigation proves that single-sex education enables teachers to address gender differences in their classroom, enhances students’ motivation, and increases students’ participation in learning process. Finally, these are beneficial to students’ academic achievement. The discussion of this investigation brings implications for education practitioner to promote the implementation of single-sex education as it has positive impacts on students’ academic achievement. In addition, the discussion is expected to have implications for policy makers to consider the needs of implementing single-sex education to narrow gender academic achievement gap.